Qu’est-ce qu’un « régime de vérité » ? - Olivier Guerrier (Les Cahiers de Framespa)
This article attempts to capture and delimit the Foucaldian notion of "régime de vérité", returning first to the importance of the question of Truth and its significance to the philosopher. It then tracks the appearance and uses of the expression, with its various avatars (“politics”, “games” ...), in the work of the latter. After which it proposes a reflexion on the meaning and intellectual issues of “Regimes and Truth”, in terms of objects, subjects, historiography, and archaeology. It concludes by specifying the applications, on specific historical fields (the first Christianity and Antiquity, in particular) that Foucault gave to the notion, in the texts and the courses of his last period in particular, and by insisting on the fertility of his investigations.